Hydromorphone for neuropathic pain in adults - Stannard, Cathy; Gaskell, Helen; Derry, Sheena; Aldington, Dominic; Cole, Peter; Cooper, Tess E.; Knaggs, Roger; Wiffen, Philip J.; Moore, R. Andrew (Wiley, 2016)
BACKGROUND